Poisoning due to an over-the-counter hypnotic, Sleep-Qik (hyoscine, cyproheptadine, valerian). Issue 834 (April 1995) - Chan, T. Y.; Tang, C. H.; Critchley, J. A.
Abstract : The clinical features and risk of hepatotoxicity of 'Sleep-Qik' (valerian dry extract 75 mg, hyoscine hydrobromide 0.25 mg, cyproheptadine hydrochloride 2 mg) were determined in 23 patients treated in our hospital between 1988 and 1991. The main clinical problems were central nervous system depression and anticholinergic poisoning. There was no clinical evidence of acute hepatitis in the 23 patients after taking an average of 2.5 g of valerian (range 0.5 to 12 g). There was no evidence of subclinical liver damage in 12 patients who had routine liver function tests performed approximately 6-12 hours after ingestion. Delayed onset of severe liver damage was excluded in 10 patients in whom a telephone follow-up was possible. However, subclinical liver dysfunction in the acute stage (onset after 12-24 hours) and in the intervening period after discharge from hospital could not be excluded. To establish the risk of hepatotoxicity in long-term users and in those taking an overdosage of valerian, a much larger study of longer duration with serial liver function tests is clearly needed.